2019
DOI: 10.1158/0008-5472.can-18-2553
|View full text |Cite
|
Sign up to set email alerts
|

MDH1 and MPP7 Regulate Autophagy in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is driven by metabolic changes in pancreatic cells caused by oncogenic mutations and dysregulation of p53. PDAC cell lines and PDAC-derived xenografts grow as a result of altered metabolic pathways, changes in stroma, and autophagy. Selective targeting and inhibition of one of these may open avenues for the development of new therapeutic strategies. In this study, we performed a genome-wide siRNA screen in a PDAC cell line using endogenous autophagy as a readout and iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…In pancreatic ductal adenocarcinoma (PDAC), the knockdown of MDH1 or inhibition of its activity could repress mitochondria respiration and influence glutamine metabolism, which enhances tumor cells' sensitivity to oxidative stress and suppresses proliferation [50]. Moreover, as a novel regulator of autophagy, MDH1 is required for autophagosome formation in the early stages of autophagy to maintain pancreatic tumor cell survival [51]. Here, we found that MDH1 is downregulated at the mRNA level in GBM based on the TCGA RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic ductal adenocarcinoma (PDAC), the knockdown of MDH1 or inhibition of its activity could repress mitochondria respiration and influence glutamine metabolism, which enhances tumor cells' sensitivity to oxidative stress and suppresses proliferation [50]. Moreover, as a novel regulator of autophagy, MDH1 is required for autophagosome formation in the early stages of autophagy to maintain pancreatic tumor cell survival [51]. Here, we found that MDH1 is downregulated at the mRNA level in GBM based on the TCGA RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between FCGR2B and prognosis in sarcoma patients had not been reported, the prognostic value of FCGR2B had been widely confirmed in other cancers, such as hepatocellular carcinoma and glioblastoma [ 36 , 42 ]. In addition, New M et.al [ 37 ] demonstrated that MPP7 is novel regulators of autophagy, which was thought to be responsible for the prognosis of pancreatic ductal adenocarcinoma. CYP2S1, described as Cytochrome P450 Family 2 Subfamily S Member 1, was reported significantly associated with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another link between autophagy and PDAC cancer stem cells is YAP/TAZ-signaling, shown to be required for cell dedifferentiation and the acquisition of self-renewing properties, i.e., stem cell formation [29]. YAP/TAZ has also been shown to be a positive autophagy regulator [30], and promotes autophagic flux by increasing Armus expression, a RAB7-GAP required for autophagosome turnover [29]. The role of autophagy in PDAC survival is not limited to tumor cells alone, but extends to the tumor microenvironment.…”
Section: Conflicting Roles Of Autophagy In Pdacmentioning
confidence: 99%